Efeitos da inoculação na compostagem e vermicompostagem de resíduos sólidos verdes urbanos - Suszek, Morgana (2005)
Green solid residues coming from urban pruner and rests of agricultural products and also swineculture effluents have been showing as one of the main problems in the urban and rural areas, because their insuitable discards, being differents enviromment impacts. A alternative in order to treatment of these residues and effluents is the aerobic composting followed by vermicomposting process. In this study, was of these evaluated the integration of the composting and vermicomposting in the biostabilization of the urban green solid residues using swine wastewater and commercial activator, furthermore being checked the quality of the earthworm humus obtained. The vermicomposts produced showed similarities in the values of the C/N ratio, nitrogen and potass, in relation to the earthworm humus made with cattle manure, indicating the possibility of the green residues use in consortium with swine wastewater in the organic fertilizer production. Metals zinc and copper in the vermicomposts were detected, however, in concentrations which don´t infer risk of the human health, plants and soil contamination. The vermicomposts from organic composts showed, in average, lower value of that metals in relation to cattle manure vermicomposts.